2017
DOI: 10.1016/j.ejca.2017.03.003
|View full text |Cite
|
Sign up to set email alerts
|

Surgery alone is sufficient therapy for children and adolescents with low-risk synovial sarcoma: A joint analysis from the European paediatric soft tissue sarcoma Study Group and the Children's Oncology Group

Abstract: Background Multimodal risk-adapted treatment is used in paediatric protocols for synovial sarcoma (SS). Retrospective analyses suggest that low-risk SS patients can be safely treated with surgery alone, but no prospective studies have confirmed the safety of this approach. This analysis pooled data from the two prospective clinical trials to assess outcomes in SS patients treated with a surgery-only approach and to identify predictors of treatment failure. Methods Patients with localised SS enrolled on the E… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

7
45
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

3
3

Authors

Journals

citations
Cited by 69 publications
(52 citation statements)
references
References 27 publications
7
45
0
Order By: Relevance
“…only local recurrences were observed at three years which were effectively salvaged. 23 This is consistent with our findings of advantage to AC only seen for stage III tumors (all at least 5 cm in size).…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…only local recurrences were observed at three years which were effectively salvaged. 23 This is consistent with our findings of advantage to AC only seen for stage III tumors (all at least 5 cm in size).…”
Section: Discussionsupporting
confidence: 92%
“…It is therefore possible that this association may exist in stage IIB patients and warrants further study. Recent study by Ferrari et al in a pediatric population with low risk synovial sarcoma ≤5 cm demonstrated that surgery alone without adjuvant therapy was associated with favorable outcomes; only local recurrences were observed at three years which were effectively salvaged . This is consistent with our findings of advantage to AC only seen for stage III tumors (all at least 5 cm in size).…”
Section: Discussionsupporting
confidence: 91%
“…That study showed higher survival rates than those previously published by pediatric groups (5‐year event free survival [EFS] and OS 80.7% and 90.7%, respectively), and described an overall response rate to chemotherapy of 55.2% (22.4% major remission plus 32.8% minor remission), with a 97% of “no progression” . The feasibility of a “surgery‐alone” strategy in low‐risk cases (small tumors completely resected at diagnosis) was confirmed by a joint pediatric European–North American study (60 patients, 3‐year EFS 90%, OS 100%; eight local recurrences and no metastatic recurrence) . However, EpSSG authors themselves emphasized the limited number of patients in each risk group and the necessity to create larger international collaboration, in particular with adult sarcoma groups, in order to create studies spanning different ages …”
Section: Synovial Sarcomamentioning
confidence: 64%
“…The feasibility of a “surgery‐alone” strategy in low‐risk cases (small tumors completely resected at diagnosis) was confirmed by a joint pediatric European–North American study (60 patients, 3‐year EFS 90%, OS 100%; eight local recurrences and no metastatic recurrence) . However, EpSSG authors themselves emphasized the limited number of patients in each risk group and the necessity to create larger international collaboration, in particular with adult sarcoma groups, in order to create studies spanning different ages …”
Section: Synovial Sarcomamentioning
confidence: 99%
“…The NRSTS 2005 protocol (Non Rhabdomyosarcoma STS Study) included a prospective nonrandomized trial on SS for the purpose of assessing the role of full-dose ifosfamide-doxorubicin chemotherapy in improving the response rates of patients with unresectable disease and examining the impact of omitting adjuvant chemotherapy in low-risk cases. This EpSSG trial (European pediatric STS Group), involving 138 patients <21 years old with SS, includes 15 different countries, with 131 centers in all [2,13]. This report showed satisfactory overall results (with 5-year EFS and OS rates of 80.7 and 90.7%, respectively) encouraging us to determine who needs chemotherapy which might be better predicted by recent findings on somatic genomic abnormalities.…”
Section: Introductionmentioning
confidence: 84%